ANALYSIS OF TOURIST SATISFACTION BASED ON 5A’S OF TOURISM ELEMENTS TOWARDS TOURIST REVISIT INTENTION TO TOMOHON CITY - Warbung, Cicilia J. E; Tulung, Joy E.; Saerang, Regina T. (Universitas Sam Ratulangi, 2021)
Tourism is one of the most expected to drive the economy of a country, the good provided of tourism would attract the attention of tourist. The biggest most concerned with tourism is the tourist who will come to visit and also satisfy tourists who come to tourist destinations so they commit to visit again. The purpose of this study is to find out more about the influence of Tourist Satisfaction based on 5A’s Tourism elements to the revisit intentions of the tourist.. This study used Structural Equation Model (SEM) t to identify the relationships between the identified factors in the model. This study conducts with 100 tourists as the respondents with maximum likelihoods. Findings of this research show that accessibilities, attractions, activities and amenities significantly influence customer satisfaction when they visit object destinations, and also customer satisfaction significantly influence tourist revisit intentions. Meanwhile accommodation cannot increase tourist customer satisfaction in this research. In order to increase and maintain customer satisfaction so they want to revisit again the tourism object, the destinations has to improve the quality to make the tourist more feel comfort when they used do tourism activities.Keyword: accessibilities, accommodations, attraction, activities, amenities, tourist satisfaction, and revisit intention